Managing interactional breakdowns with children with ASD: Therapists' practices when directives face challenges in therapeutic interactions. - Ma, Xiaoxin; Ma, Wen; Zhang, Shuai (Clinical Linguistics & Phonetics, 2026)
Effective interventions to promote language competence, cognitive abilities and integrate these skills into daily activities for children with autism spectrum disorder (ASD) often involve providing guidance and training through specific tasks, typically delivered by speech and language therapists through directive interactions. However, engaging children with ASD in such activities is not straightforward and often fraught with challenges. Yet we know very little about how practitioners cope when the interaction breaks down, for example, due to misunderstandings or failures to engage. This study employs a conversation analytic approach to uncover therapists' intricate practices for managing breakdowns in therapeutic interactions. Over 200 hours of naturally occurring interactions between seven Mandarin-speaking children and their therapists were recorded and analysed. Using Conversation Analysis, we identified and analysed 1062 directive turns issued by therapists and subsequent responses of the children. The findings are in three aspects: 1) A crucial and effective premise for increasing engagement and improving the quality of therapeutic interactions lies in recognising, ascribing and utilising the specific interactive modes of children with ASD, including their repeated utterances and prosodic resources. 2) Therapists' strategies are successful when they flexibly address and adapt the format of directives through tailored verbal iteration and embodied solicitation. 3) The importance of timing underscores the increased opportunities to positively influence turn-taking in children with ASD. It is proposed that practitioners can enhance their understanding of children with ASD by incorporating the profiling of interaction into their assessments and interventions, adapting ways to align with the unique patterns of children with ASD.